Laser-induced breakdown spectroscopy applied to the rapid identification of different types of polyethylene used for toy manufacturing - Costa, Vinicius Câmara; Pereira, Fabíola Manhas Verbi [UNESP] (Wiley, 2020)
The identification of plastics is of great importance to recycling companies, as the littering of plastic wastes has rapidly increased because of the extensive use of plastics. To maintain the economics of recycling extremely large volumes of waste materials, rapid and accurate identification of these plastics is crucial. In this study, we demonstrate the efficacy of laser-induced breakdown spectroscopy (LIBS) in the rapid identification of high-density polyethylene (HDPE) and low-density polyethylene (LDPE) used for toy manufacturing. For data analysis of the LIBS spectra, multivariate data analysis using principal component analysis (PCA) was utilized. The analyses of the data clearly showed that the elemental and molecular information obtained from LIBS is effective in the identification of three types of polyethylene. The proposed method was successfully applied and can be used as an alternative to the traditional methods used for analyses of plastics.
Keywords: LIBS; PCA; plastics; polyethylene; recycling; toy